Structural and quantitative similarities and differences of homoparadigms in Belarusian and Italian languages (based on the material of explanatory dictionaries) - Skromblevich, Valeria B. (Journal of the Belarusian State University. Philology, 2025)
The structural and quantitative characteristics of homonymous paradigms in Belarusian and Italian languages are defined and compared. The general and specific aspects of approaches to the description of homonyms in lexicographical sources are specified, quantitative and structural similarities and differences between homoparadigms are revealed. Depending on the characteristics of the component of homoparadigm, the following types were identified: identical and mixed (according to the quantitative parameter); homogeneous and combined (according to the morphological affiliation of the component); graphical and phonetical-graphical (according to the form of coincidence of structural units). According to functional and stylistic features, seven types were identified, five of which are common to both languages.